Controllable Water Droplet for Microsystem Actuators: An Experimental Analysis - Song, Byung-Keun; Mulla, Tausif; Choi, Seung-Bok (Frontiers in Materials, 2018)
Dielectric liquids such as water exhibit significant displacement under a high electric field. Alike smart materials, oscillations of such dielectric liquids can be manipulated using controlled voltage. This study investigates basic actuation property of a water droplet by applying an electrical voltage across two parallel plate electrodes covered by a thin dielectric material. The dynamic characteristics of the water droplet response are evaluated using step input voltage. The sensitivity of the droplet response to a change in the system parameters is also analyzed. The procedure of analysis of variance is adopted to analyze the effectiveness and the combined effect of different parameters on the response. Accordingly, several parameters such as the relative permittivity of the dielectric substrate, thickness of the dielectric substrates, gap between the electrodes, relative permittivity of the dielectric fluid, and applied electric voltage are chosen as control factors. The steady-state response and damping ratio are considered as the output responses. The quadratic regression model associated with the response surface methodology is thereafter used to correlate the output response with the system parameters. It is shown that the gap between the electrodes is the dominant factor affecting the steady-state response whereas the thickness of the dielectric substrate is the dominant factor affecting the damping ratio. In addition, a good consistency is observed between the predicted and experimental responses.